PENGGUNAAN MEDIA VIDEO UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SENI BUDAYA MATERI SENI RUPA - YULIA CITRA, Dra. Ernis, M.Pd. (Universitas Negeri Padang, 2019)
This research is conducted in order to improve student achievement on art in the topic of drawing poster. The indicator used are videos from students in VIII.3 class of SMPN 3 Padang. The type of this research is class-act observations. This research was conducted for two phase. The tools used in data collecting are documentations teachers observation sheets, students observation sheets, and academic performance test, and academic performance format. The data is processed by using percentage formula. The result shous that the students achievement increased. The average achievement for phase I is 77,76 and 88,06 for phase II. In this case an increase of 10,3 from cycle I to cycle II. In summary, the use of video can increase the students achievement.Kata Kunci: Learning media, learning video, learning outcomes.